IMABASE: A new set of 313 colourised line drawings standardised in French for name agreement, image agreement, conceptual familiarity, age-of-acquisition, and imageability. Issue 11 (November 2020) - Bonin, Patrick; Poulin-Charronnat, Bénédicte; Lukowski Duplessy, Helle; Bard, Patrick; Vinter, Annie; Ferrand, Ludovic; Méot, Alain
We provide normative data for a new set of 313 colourised line drawings. The drawings were standardised on name agreement ( N = 60 participants), image agreement ( N = 34), conceptual familiarity ( N = 36), age of acquisition ( N = 35), and imageability ( N = 35). Objective visual complexity measures are given for the pictures, and objective word frequencies are provided for the modal names of the drawings. Reliability measures for the collected norms are very high. There are high levels of agreement between the names given by the participants and the drawings and comparative analyses indicate that the distribution of name agreement scores is very similar in both our own database and the MultiPic database (Duñabeitia et al., 2018). A novel "picture-choice task" used to assess name-image agreement ( N = 30) reveals that the great majority of the IMABASE pictures that are also present in MultiPic are rated as providing better pictorial representations of the corresponding concepts. Finally, most of the correlations are comparable with those reported in other normative studies on colourised drawings. The whole set of pictures is freely available from https://leadserv.u-bourgogne.fr/ lead/imabase/ and the norms are available as Supplementary Material.